China's challenge to world development paradigms. Issue 1 (2nd January 2021) - Rayman, Joshua
ABSTRACT: The past forty years of world development have seen multiple operational frameworks, most notably, the neoliberal Washington Consensus or structural adjustment policies (1981–2001), the international development framework guided by the United Nations Millennium Development Goals (MDG, 2000–2015), and the Chinese Economic Model or Beijing Consensus emerging from Deng Xiaoping's reforms (1978-present). I criticize the Washington Consensus as an economic, ethical-political, and environmental failure. I cast doubt both on the novelty and efficacy of the frameworks to enact the Millennium Development Goals by showing that they largely repackage structural adjustment policies in democratic terms and contribute far less to recent global successes than alternative Chinese and Indian models. I describe the Chinese Economic Model as both a far more successful domestic economic alternative to the hegemonic Western models and a problematic export with the potential to transform as well as to destabilize developing countries. Finally, I articulate conditions for an alternative that would enact the democratic rhetoric of the Millennium Development Goals, learn from the domestic scale of infrastructure and education spending, the national focus, local implementation, and recent environmental experiments of the Chinese Economic Model, and recognize the environment's fundamental significance to development.